The Combination Of Balance Exercises And Tandem Walking Exercises In Improving Body Balance In Elderly Patients With Hypertension - Erri Fitriyani; Adi Isworo; Sunarko; Nita Tri Septiana; Hermani Triredjeki; Suharsono (Journal of Tropical Diseases and Health Science, 2026)
Background: Hypertension is a common non-communicable disease among the elderly and can lead to various complications. One of the frequent consequences is impaired body balance, which increases the risk of falls and reduces quality of life. Age-related physiological changes, such as decreased muscle strength and reduced vascular elasticity, contribute to balance instability. The combination of balance exercise and tandem walking exercise may be an effective intervention to improve balance in elderly individuals with hypertension. This study aimed to determine the effectiveness of a combination of balance exercise and tandem walking exercise in improving body balance among elderly patients with hypertension. This pre-experimental study used a one-group pre-test and post-test design and was conducted in the Bandongan Primary Health Care Center area, Magelang, from January to June 2025. The population consisted of 527 elderly individuals with hypertension aged ≥ 60 years, and 45 participants were selected using purposive sampling. Body balance was assessed using the Timed Up and Go Test (TUGT) before and after the intervention. Data were analyzed using the Shapiro–Wilk normality test and the Wilcoxon test. The Wilcoxon test showed a p-value of 0.000 (p < 0.05), indicating a significant improvement in body balance after the intervention. The combination of balance exercise and tandem walking exercise is effective in improving body balance among elderly patients with hypertension.